Multicentric Squamous Cell Carcinoma with the Involvement of the Ocular Annexes in a Dog - Bezerra, Karla Priscila Garrido; de Souza, Maria de Fátima; Borges, Olivia Maria Moreira; de Lucena, Ricardo Barbosa; Talieri, Ivia Carmem; de Souza, Almir Pereira (Acta Scientiae Veterinariae, 2020)
Background: The cutaneous squamous cell carcinoma (cSCC) is considered to be a frequent neoplasm in dogs, however, its origin in ocular annexes, especially in relation to the conjuctival location, is a rare finding in dogs. Therefore, it was aimed to report the occurrence of a multicentric SCC, with the involvement of ocular annexes in a dog, emphasizing its clinical characteristics and histopathological findings. Case: A 6-year-old non-castrated white-coated Pitbull dog was attended, with a history of increased volume and bloody secretion in the left eye, with an evolution of approximately six months. By means of general physical examination, ulcerated lesions in the foreskin and scrotum were found. During the ophthalmologic examination was identified an extensive and irregular exophytic mass, of a reddish color and with a cauliflower-like appearance, located in the inferior bulbar conjunctiva and third eyelid of the left eye, accompanied by a large quantity of piosanguinolenta secretion, mainly during manipulation. Other alterations were observed, such as, meibomitis, conjuctival hyperemia, hypopyon, corneal edema and loss of sight. In the right eye, the only alteration found was conjunctival hyperemia. The hemograma revealed discreet anemia; the serum biochemical profile was inside the normal range and there was no evidence of metastasis in the imaging examinations. The animal was submitted to the incisional biopsy of the lesions for histopathological analysis, which revealed a proliferation of neoplastic epithelial cells, highly pleomorphic, composed of eosinophilic cytoplasm, which varied from scarce to moderate, of indistinct borders, with a large nucleus and loose chromatin and large and evident nucleolus, compatible with SCC, enabling, also, the classification as multicentric due to the multiple localizations. Additionally, associated to the conjunctival tumor, there was necrosis and mixed inflammatory infiltration; in the scrotum and conjunctiva, the cells presented more accentuated pleomorphism, with the presence of dyskeratosis and little formation of keratin pearls; however in the prepuce, there was abundant formation of keratin pearls in the midst of the tumor. In the immunohistochemical analysis, the neoplastic cells demonstrated strong and uniform cytoplasmic immunoreactivity for pancytokeratin. It was recommended the exenteration of the left eye followed by the introduction of acrylic resin intraorbital implant, together with the resection of the neoplasm from the scrotum and foreskin, associated with cryotherapy. However, the owner was reluctant to the proposed treatment and opted for the euthanasia of the animal, not consenting to the performance of the necropsy. Discussion: The etiological factors related to the development of the SCCs, especially concerning those of the ocular and periocular region, in dogs and cats, are still not well defined. However, the overexposure to the ultraviolet radiation has been pointed as the main etiological factor, especially in tropical and high-altitude regions. Indeed, the characteristics of the region in which the animal resided, associated to its way of life and its phenotypical characteristics suggested that the chronic exposure to ultraviolet radiation would be the most plausible cause related to the emergence of the multicentric SCC of this case. Thus, it is suggested that, while the physiopathology of the neoplasm has still yet not been elucidated, it must be avoided that the dogs, with these characteristics, expose themselves too much to solar radiation.